2009
DOI: 10.3390/molecules14093187
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, ex Vivo and in Vitro Hydrolysis Study of an Indoline Derivative Designed as an Anti-Inflammatory with Reduced Gastric Ulceration Properties

Abstract: The compound 1-(2,6-dichlorophenyl)indolin-2-one (1), planned as a pro-drug of diclofenac (2), was easily synthesized in 94% yield by an intramolecular reaction in the presence of coupling agent (i.e., EDC). Compound 1 showed anti-inflammatory and analgesic activity without gastro-ulcerogenic effects. The chemical and enzymatic hydrolysis profile of the lactam derivative 1 does not indicate conversion to diclofenac (2). This compound is a new non-ulcerogenic prototype for treatment of chronic inflammatory dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…All results were statistically significant when compared to the aqueous solution of sodium carboxymethylcellulose (0.5% w / v ) used as the control (not shown). At 300 μmol/kg, the anti-inflammatory activity was the same observed in our previous at 100 μmol/kg [16]. …”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…All results were statistically significant when compared to the aqueous solution of sodium carboxymethylcellulose (0.5% w / v ) used as the control (not shown). At 300 μmol/kg, the anti-inflammatory activity was the same observed in our previous at 100 μmol/kg [16]. …”
Section: Resultssupporting
confidence: 84%
“…Preliminar in vivo pharmacokinetic study demonstrated bioconversion of diclofenac prodrug to parental drug after administration, despite in vitro chemical and plasmatic studies have not demonstrated this conversion [16]. These results allow us to corroborate the success of our molecular modification strategy.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations